Together With Veterans: VA National Strategy Alignment and Lessons Learned from Community‐Based Suicide Prevention for Rural Veterans. Issue 3 (16th January 2020) - Monteith, Lindsey L.; Wendleton, Leah; Bahraini, Nazanin H.; Matarazzo, Bridget B.; Brimner, Gina; Mohatt, Nathaniel V.
Abstract : Background: Rural veterans are at increased risk for dying by suicide compared with urban veterans, yet interventions for preventing suicide among rural veterans have been limited. Objectives: (1) Describe how Together With Veterans (TWV), a community‐based intervention to prevent suicide among veterans in rural communities, aligns with the VA National Strategy for Preventing Veteran Suicide; (2) share lessons learned while beginning to implement TWV in rural communities. Methods: Together With Veterans is being implemented in four rural communities and comprises six suicide prevention best practices: (1) reducing stigma and promoting help‐seeking; (2) lethal means safety, with an emphasis on firearms; (3) gatekeeper training; (4) training primary care providers; (5) improving access to crisis services; and (6) enhancing support for high‐risk veterans. Results: Together With Veterans best practices align with most, but not all, of the strategies in the VA National Strategy for Preventing Veteran Suicide. Community veteran partners have shown a willingness to collaborate and provide local leadership, enthusiasm, and a sense of duty. Conclusions: By supporting and facilitating local veteran leaders and their community partners in increasing suicide prevention knowledge, public awareness, and resources, we propose that TWV offers an acceptable and feasible approach that builds on the strengths of rural communities. Systematic evaluation is warranted.